High-performance antibacterial thermoplastic resin and preparation method thereof
By introducing Ag-MgO load-modified PPTA fibers into thermoplastic resins, the problem of insufficient mechanical properties and antibacterial properties of thermoplastic resins in specific application fields is solved, and the preparation of high-performance antibacterial thermoplastic resin composites is realized, which significantly improves the material Mechanical and antibacterial properties.
Patent Information
- Application Number
- CN202310950724.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The existing thermoplastic resins have limited mechanical properties and antibacterial properties in some specific application fields, making it difficult to meet the high requirements for antibacterial and mechanical properties.
By synthesizing Ag-MgO-loaded modified PPTA fibers and combining them with thermoplastic resins, a high-performance antibacterial thermoplastic resin composite material is formed. The method includes reacting nanomagnesium oxide and silver nitrate with a reducing agent to produce Ag-MgO, which is then loaded onto the PPTA fibers, and processing and drying them by a pad mill to obtain the modified fibers.
This method not only improves the mechanical properties of the thermoplastic resin, but also significantly improves its antibacterial properties, which can effectively adsorb and kill bacteria and extend the service life of the material.
Smart Images

Figure BDA0004368249340000081 
Figure BDA0004368249340000101 
Figure BDA0004368249340000111
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a high-performance antibacterial thermoplastic resin and a preparation method thereof. Background Art
[0002] Thermoplastic resin is a widely used polymer polyester resin. Thermoplastic resin has the advantages of good fatigue resistance, good heat resistance, excellent dimensional stability, etc. However, in some specific application fields, the mechanical properties and antibacterial properties of thermoplastic resin are very high. For example, when thermoplastic resin is used in lunch boxes, it is not only resistant to steam, but also can be used in microwaves or refrigerators. However, plastic lunch boxes require antibacterial properties because during use, microorganisms in the form of bacteria, molds, etc. as pathogens can easily infect humans, animals and plants, cause diseases, and endanger human health and life. This limits the application of thermoplastic resin composites in some specific fields.
[0003] At present, in order to improve the antibacterial properties of thermoplastic resins, the main way is to add antibacterial agents to them. Antibacterial agents refer to chemical substances that can keep the growth or reproduction of certain microorganisms (bacteria, fungi, yeasts, algae and viruses, etc.) below the necessary level within a certain period of time. Antibacterial agents are substances or products with antibacterial and bactericidal properties, such as silver. The antibacterial mechanism of silver ions and their compounds is a contact reaction antibacterial mechanism. The contact reaction of silver ions causes the destruction of common components of microorganisms or functional disorders. When a trace amount of silver ions reaches the cell membrane of microorganisms, because the latter is negatively charged, the two are firmly adsorbed by Coulomb attraction. The silver ions penetrate the cell wall and enter the cell, and react with SH groups to coagulate proteins, destroy the activity of cell synthases, and the cells lose the ability to divide and proliferate and die. Silver ions can also destroy the electron transport system, respiratory system and material transport system of microorganisms.
[0004] Although nanosilver is a commonly used inorganic antibacterial agent with good biocompatibility, environmental safety and long-lasting antibacterial properties, adding it directly to the plastic matrix will easily lead to the agglomeration of the nano antibacterial agent, which will affect its original antibacterial properties to a certain extent.
[0005] In view of these deficiencies, the present invention innovatively synthesizes a high-performance antibacterial thermoplastic resin composite material, which has excellent mechanical properties and antibacterial properties. This thermoplastic resin composite material has not been reported so far, which has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention
[0006] In view of this, the present invention innovatively synthesizes a high-performance antibacterial thermoplastic resin and a preparation method thereof, which has excellent antibacterial and mechanical properties, and solves the technical problem of limited antibacterial and mechanical properties of thermoplastic resins in the prior art.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A high-performance antibacterial thermoplastic resin, which consists of the following components in parts by weight:
[0009] Thermoplastic resin 80-100 parts
[0010] Modified PPTA fiber 10-16 parts
[0011] Antioxidant 0.1-0.5 parts
[0012] The modified PPTA fiber is Ag-MgO loaded PPTA fiber.
[0013] In a further embodiment, the method for preparing the modified PPTA fiber comprises the following steps:
[0014] (1) adding nano magnesium oxide and silver nitrate into a reducing agent aqueous solution, stirring for reaction, filtering, washing and drying to obtain Ag-MgO;
[0015] (2) adding Ag-MgO to water and stirring to react to prepare a solution;
[0016] (3) Immersing the PPTA fiber in the solution of step (2), and after being treated by a padding machine, washing and drying, the Ag-MgO loaded PPTA fiber is obtained, namely, the modified PPTA fiber.
[0017] Preferably, the mass ratio of nano-magnesium oxide, silver nitrate and reducing agent in step (1) is (30-40): (30-36): (0.2-0.4);
[0018] The reducing agent is sodium bisulfite, sodium borohydride or lithium aluminum hydride,
[0019] The stirring reaction is carried out at 60-80°C for 6-8h.
[0020] Preferably, the mass ratio of Ag-MgO to deionized water in step (2) is (30-40): (80-90);
[0021] The stirring reaction is carried out at 30-50°C for 6-8h.
[0022] Preferably, the padding treatment in step (3) is repeated three times, and the pressure of the padding treatment is 0.2-0.3 MPa and the speed is 20-40 rpm;
[0023] Dry in a vacuum oven at 60-80℃ for 10-14h.
[0024] In a further embodiment, the antioxidant is one or a mixture of tris(2,4-di-tert-butyl)phenyl phosphite (referred to as Irganox 168), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (referred to as Irganox 1010) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (referred to as Irganox 1330).
[0025] In a further embodiment, the thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT), and polyamide 6 (PA6).
[0026] The second object of the present invention is to provide a method for preparing the above-mentioned high-performance antibacterial thermoplastic resin, comprising the following steps:
[0027] (1) Weigh 80-100 parts of thermoplastic resin, 10-16 parts of modified PPTA fiber, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture;
[0028] (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention prepares a composite antibacterial agent Ag-MgO by an in-situ reduction method, and then loads it on PPTA fiber to form Ag-MgO@PPTA fiber. The modified PPTA fiber prepared by this process can not only improve the physical properties of thermoplastic resin, but also improve its antibacterial properties.
[0031] (2) The composite antibacterial agent Ag-MgO in the modified PPTA fiber of the present invention can be adsorbed on the bacterial cell wall, causing cell wall perforation and damage, leading to cell death. In addition, the composite antibacterial agent Ag-MgO interacts with the thiol group on the protein, inhibits the activity of the protein, and ultimately kills the bacteria, which can well improve the antibacterial properties of the thermoplastic resin.
[0032] (3) Compared with commercially available PPTA fibers, the modified PPTA fibers of the present invention load Ag-MgO on the PPTA fibers, which can not only improve the mechanical properties of the thermoplastic resin, but also improve its antibacterial properties, which has great promotion value. DETAILED DESCRIPTION
[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0035] The raw materials used in the following examples are as follows:
[0036] PBT (model 2002U), Polyplastics, Japan;
[0037] PP (model Z30S), Maoming Petrochemical;
[0038] PE (model 5070), Panjin ethylene;
[0039] PA6 (model CM1017), Toray, Japan;
[0040] PS (model 350), Guoqiao, Taiwan Province of China;
[0041] Nano magnesium oxide, Jiujiang Hengtong Chemical Co., Ltd.;
[0042] Silver nitrate, Tongbai Hongxin New Materials Co., Ltd.; deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.;
[0043] Sodium bisulfite, Jinan Xinchaorui Chemical Co., Ltd.;
[0044] PPTA fiber, Jiangxi Jerman Special Fiber Products Co., Ltd.;
[0045] Antioxidant (model Irganox168, Irganox1010, Irganox1330), BASF.
[0046] Preparation Example 1
[0047] (1) Weigh 300 g of nano magnesium oxide (MgO), 300 g of silver nitrate, 800 g of deionized water, and 2 g of reducing agent sodium bisulfite, place them in a reaction vessel, stir and react at 60° C. for 6 h to prepare solution A;
[0048] (2) filtering, washing, and drying solution A to obtain Ag-MgO;
[0049] (3) Weigh 300 g of Ag-MgO and 800 g of deionized water, place in a reaction vessel, and stir at 30° C. for 6 h to prepare solution B;
[0050] (4) The PPTA fiber was immersed in solution B and subjected to a rolling process by a rolling mill at a pressure of 0.2 MPa and a speed of 40 rpm. The rolling process was repeated three times, followed by washing and drying in a vacuum drying oven at 60°C for 10 h to obtain Ag-MgO loaded PPTA fiber, i.e., modified PPTA fiber M1.
[0051] The padding mill in step (4) has a pressure of 0.2 MPa and a speed of 20 rpm.
[0052] Example 1
[0053] (1) Weigh 80 parts of PP, 10 parts of modified PPTA fiber M1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;
[0054] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.
[0055] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 235°C, the temperature of the third temperature zone is 235°C, the temperature of the fourth temperature zone is 235°C, the temperature of the fifth temperature zone is 235°C, the temperature of the sixth temperature zone is 235°C, the head temperature of the twin-screw extruder is 235°C, and the screw speed is 235r / min.
[0056] Comparative Example 1
[0057] (1) Weigh 80 parts of PP, 10 parts of Ag-MgO prepared in Preparation Example 1, and 0.1 parts of Irganox 1010, mix and stir to obtain a mixture;
[0058] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.
[0059] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 235°C, the temperature of the third temperature zone is 235°C, the temperature of the fourth temperature zone is 235°C, the temperature of the fifth temperature zone is 235°C, the temperature of the sixth temperature zone is 235°C, the head temperature of the twin-screw extruder is 235°C, and the screw speed is 235r / min.
[0060] Comparative Example 2
[0061] (1) Weigh 80 parts of PP, 10 parts of commercially available PPTA fiber, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;
[0062] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D2.
[0063] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 235°C, the temperature of the third temperature zone is 235°C, the temperature of the fourth temperature zone is 235°C, the temperature of the fifth temperature zone is 235°C, the temperature of the sixth temperature zone is 235°C, the head temperature of the twin-screw extruder is 235°C, and the screw speed is 235r / min.
[0064] The PP composite materials prepared in the above Example 1 and Comparative Example 1 and Comparative Example 2 were made into strips for testing using an injection molding machine. The test data are as follows:
[0065]
[0066] It can be seen from the above table that the mechanical properties of Example 1 are generally better than those of Comparative Example 1, and the antibacterial properties are better than those of Comparative Example 2. In general, the mechanical properties and antibacterial properties of Example 1 are the best.
[0067] Preparation Example 2
[0068] (1) Weigh 400 g of nano magnesium oxide (MgO), 360 g of silver nitrate, 1.2 kg of deionized water, and 4 g of reducing agent sodium bisulfite, place them in a reaction vessel, stir and react at 80° C. for 8 h to prepare solution A;
[0069] (2) filtering, washing, and drying solution A to obtain Ag-MgO;
[0070] (3) Weigh 400 g of Ag-MgO and 900 g of deionized water, place in a reaction vessel, and stir at 50° C. for 8 h to prepare solution B;
[0071] (4) The PPTA fiber was immersed in solution B and subjected to a rolling process by a rolling mill at a pressure of 0.3 MPa and a speed of 20 rpm. The above rolling process was repeated three times, and the fiber was washed and dried in a vacuum drying oven at 80°C for 14 h to obtain Ag-MgO loaded PPTA fiber, i.e., modified PPTA fiber M2.
[0072] The padding mill in step (4) has a pressure of 0.3 MPa and a speed of 40 rpm.
[0073] Example 2
[0074] (1) Weigh 100 parts of PBT, 16 parts of modified PPTA fiber M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0075] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.
[0076] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 245°C, the temperature of the third temperature zone is 245°C, the temperature of the fourth temperature zone is 245°C, the temperature of the fifth temperature zone is 245°C, the temperature of the sixth temperature zone is 245°C, the head temperature of the twin-screw extruder is 245°C, and the screw speed is 300r / min.
[0077] Comparative Example 3
[0078] (1) Weigh 100 parts of PBT, 16 parts of Ag-MgO prepared in Preparation Example 2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0079] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D3.
[0080] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 245°C, the temperature of the third temperature zone is 245°C, the temperature of the fourth temperature zone is 245°C, the temperature of the fifth temperature zone is 245°C, the temperature of the sixth temperature zone is 245°C, the head temperature of the twin-screw extruder is 245°C, and the screw speed is 300r / min.
[0081] Comparative Example 4
[0082] (1) Weigh 100 parts of PBT, 16 parts of commercially available PPTA fiber, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0083] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D4.
[0084] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 245°C, the temperature of the third temperature zone is 245°C, the temperature of the fourth temperature zone is 245°C, the temperature of the fifth temperature zone is 245°C, the temperature of the sixth temperature zone is 245°C, the head temperature of the twin-screw extruder is 245°C, and the screw speed is 300r / min.
[0085] The PBT composite materials prepared in the above Example 2 and Comparative Examples 3 and 4 were made into test strips by injection molding machine, and the test data are as follows:
[0086]
[0087]
[0088] It can be seen from the above table that the mechanical properties of Example 2 are better than those of Comparative Example 3, and the antibacterial properties are better than those of Comparative Example 4. In general, the mechanical properties and antibacterial properties of Example 2 are the best.
[0089] Preparation Example 3
[0090] (1) Weigh 350 g of nano magnesium oxide (MgO), 330 g of silver nitrate, 1.0 kg of deionized water, and 3 g of reducing agent sodium bisulfite, place them in a reaction vessel, and stir at 70° C. for 7 h to prepare solution A;
[0091] (2) filtering, washing, and drying solution A to obtain Ag-MgO;
[0092] (3) Weigh 350 g of Ag-MgO and 850 g of deionized water, place in a reaction vessel, and stir at 40° C. for 7 h to prepare solution B;
[0093] (4) The PPTA fiber was immersed in solution B and subjected to padding treatment by a padding machine at a pressure of 0.25 MPa and a speed of 30 rpm. The above padding process was repeated three times, and the fiber was washed and dried in a vacuum drying oven at 70° C. for 12 h to obtain Ag-MgO loaded PPTA fiber, i.e., modified PPTA fiber M3.
[0094] The padding mill in step (4) has a pressure of 0.25 MPa and a speed of 30 rpm.
[0095] Example 3
[0096] (1) Weigh 90 parts of PE, 13 parts of modified PPTA fiber M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;
[0097] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.
[0098] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 140°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 185°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 185°C, the temperature of the sixth temperature zone is 185°C, the head temperature of the twin-screw extruder is 185°C, and the screw speed is 300r / min.
[0099] Comparative Example 5
[0100] (1) Weigh 90 parts of PE, 13 parts of Ag-MgO prepared in Preparation Example 3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir to obtain a mixture;
[0101] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D5.
[0102] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 140°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 185°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 185°C, the temperature of the sixth temperature zone is 185°C, the head temperature of the twin-screw extruder is 185°C, and the screw speed is 300r / min.
[0103] Comparative Example 6
[0104] (1) Weigh 90 parts of PE, 13 parts of commercially available PPTA fiber, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir to obtain a mixture;
[0105] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D6.
[0106] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 140°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 185°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 185°C, the temperature of the sixth temperature zone is 185°C, the head temperature of the twin-screw extruder is 185°C, and the screw speed is 300r / min.
[0107] The PE composite materials prepared in the above Example 3 and Comparative Examples 5-6 were made into test strips by injection molding machine, and the test data are as follows:
[0108]
[0109] It can be seen from the above table that the mechanical properties of Example 3 are better than those of Comparative Example 5, and the antibacterial properties are better than those of Comparative Example 6. In general, the mechanical properties and antibacterial properties of Example 3 are the best.
[0110] Preparation Example 4
[0111] (1) Weigh 335 g of nano magnesium oxide (MgO), 345 g of silver nitrate, 995 g of deionized water, and 3.5 g of reducing agent sodium bisulfite, place them in a reaction vessel, and stir at 75° C. for 8 h to prepare solution A;
[0112] (2) filtering, washing, and drying solution A to obtain Ag-MgO;
[0113] (3) Weigh 385 g of Ag-MgO and 885 g of deionized water, place in a reaction vessel, and stir at 45 °C for 6 h to prepare solution B;
[0114] (4) The PPTA fiber was immersed in solution B and subjected to a rolling process by a rolling mill at a pressure of 0.2-0.3 MPa and a speed of 28 rpm. The above rolling process was repeated three times, and the fiber was washed and dried in a vacuum drying oven at 75°C for 13 h to obtain Ag-MgO loaded PPTA fiber, i.e., modified PPTA fiber M4.
[0115] The padding mill in step (4) has a pressure of 0.28 MPa and a speed of 38 rpm.
[0116] Example 4
[0117] (1) Weigh 92.5 parts of PA6, 15 parts of modified PPTA fiber M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0118] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.
[0119] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 265°C, the temperature of the fourth temperature zone is 265°C, the temperature of the fifth temperature zone is 265°C, the temperature of the sixth temperature zone is 265°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0120] Comparative Example 7
[0121] (1) Weigh 92.5 parts of PA6, 15 parts of Ag-MgO prepared in Preparation Example 4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0122] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D7.
[0123] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 265°C, the temperature of the fourth temperature zone is 265°C, the temperature of the fifth temperature zone is 265°C, the temperature of the sixth temperature zone is 265°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0124] Comparative Example 8
[0125] (1) Weigh 92.5 parts of PA6, 15 parts of commercially available PPTA fiber, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0126] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D7.
[0127] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 265°C, the temperature of the fourth temperature zone is 265°C, the temperature of the fifth temperature zone is 265°C, the temperature of the sixth temperature zone is 265°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0128] The PA6 composite materials prepared in the above Example 4 and Comparative Examples 7-8 were made into strips by injection molding machine for testing. The test data are shown in the following table:
[0129]
[0130] It can be seen from the above table that the mechanical properties of Example 4 are better than those of Comparative Example 7, and the antibacterial properties are better than those of Comparative Example 8. In general, the mechanical properties and antibacterial properties of Example 4 are the best.
[0131] Preparation Example 5
[0132] (1) Weigh 315 g of nano magnesium oxide (MgO), 355 g of silver nitrate, 1.15 kg of deionized water, and 4 g of reducing agent sodium bisulfite, place them in a reaction vessel, and stir at 77° C. for 8 h to prepare solution A;
[0133] (2) filtering, washing, and drying solution A to obtain Ag-MgO;
[0134] (3) Weigh 395 g of Ag-MgO and 825 g of deionized water, place in a reaction vessel, and stir at 45 °C for 8 h to prepare solution B;
[0135] (4) The PPTA fiber was immersed in solution B and subjected to a rolling process by a rolling mill at a pressure of 0.3 MPa and a speed of 35 rpm. The above rolling process was repeated three times, and the fiber was washed and dried in a vacuum drying oven at 75°C for 13 h to obtain Ag-MgO loaded PPTA fiber, i.e., modified PPTA fiber M5.
[0136] Preferably, the padding mill treatment in step (4) has a pressure of 0.21 MPa and a speed of 38 rpm.
[0137] Example 5
[0138] (1) Weigh 85 parts of PS, 14 parts of modified PPTA fiber M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;
[0139] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material P5.
[0140] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 225°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 225°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0141] Comparative Example 9
[0142] (1) Weigh 85 parts of PS, 14 parts of Ag-MgO prepared in Preparation Example 4, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;
[0143] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D9.
[0144] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 225°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 225°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0145] Comparative Example 10
[0146] (1) Weigh 85 parts of PS, 14 parts of commercially available PPTA fiber, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;
[0147] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D9.
[0148] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 225°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 225°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0149] The PS composite materials prepared in the above Example 5 and Comparative Examples 9-10 were made into strips by injection molding and tested. The test data are shown in the following table:
[0150]
[0151]
[0152] It can be seen from the above table that the mechanical properties of Example 5 are better than those of Comparative Example 9, and the antibacterial properties are better than those of Comparative Example 10. In general, the mechanical properties and antibacterial properties of Example 5 are the best.
[0153] This shows that the thermoplastic resin composite material prepared by the method provided by the present invention has excellent mechanical properties and antibacterial properties, and can expand the application field of the thermoplastic resin composite material.
[0154] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0155] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high-performance antibacterial thermoplastic resin composite material, characterized in that: It is composed of the following components by weight: Thermoplastic resin 80-100 parts Modified PPTA fiber 10-16 parts Antioxidant 0.1-0.5 parts The modified PPTA fiber is Ag-MgO loaded PPTA fiber.
2. A high-performance antibacterial thermoplastic resin composite material according to claim 1, characterized in that: The preparation method of the modified PPTA fiber comprises the following steps: (1) adding nano magnesium oxide and silver nitrate into a reducing agent aqueous solution, stirring for reaction, filtering, washing and drying to obtain Ag-MgO; (2) adding Ag-MgO to water and stirring to react to prepare a solution; (3) Immersing the PPTA fiber in the solution of step (2), and after being treated by a padding machine, washing and drying, the Ag-MgO loaded PPTA fiber is obtained, namely, the modified PPTA fiber.
3. A high-performance antibacterial thermoplastic resin composite material according to claim 2, characterized in that: The mass ratio of nano magnesium oxide, silver nitrate and reducing agent in step (1) is (30-40): (30-36): (0.2-0.4).
4. The high-performance antibacterial thermoplastic resin composite material according to claim 2, characterized in that: The reducing agent is sodium bisulfite, sodium borohydride or lithium aluminum hydride.
5. The high-performance antibacterial thermoplastic resin composite material according to claim 2, characterized in that: The mass ratio of Ag-MgO and deionized water in step (2) is (30-40):(80-90).
6. The high-performance antibacterial thermoplastic resin composite material according to claim 2, characterized in that: The stirring reaction in step (1) is carried out at 60-80° C. for 6-8 hours; The stirring reaction in step (2) is carried out at 30-50° C. for 6-8 hours.
7. The high-performance antibacterial thermoplastic resin composite material according to claim 2, characterized in that: The padding treatment in step (3) is repeated three times, the pressure of the padding treatment is 0.2-0.3 MPa, and the speed is 20-40 rpm; Dry in a vacuum oven at 60-80℃ for 10-14h.
8. The high-performance antibacterial thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene or a mixture of several thereof.
9. The high-performance antibacterial thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin includes PP, PBT, PE, PS or PA.
10. A method for preparing a high-performance antibacterial thermoplastic resin composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh 80-100 parts of thermoplastic resin, 10-16 parts of modified PPTA fiber, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture; (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.
Citation Information
Patent Citations
Preparation method of antibacterial agent, thermoplastic resin composite material and preparation method of thermoplastic resin composite material
CN113621181A
Heat-conducting antibacterial thermoplastic resin composite material and preparation method thereof
CN116285112A